PJMHS 2022
DOI: 10.53350/pjmhs22164298
|View full text |Cite
|
Sign up to set email alerts
|

Common Hematological Abnormalities in patients with Malaria presenting at Saidu Teaching Hospital, Swat Pakistan

Abstract: Objectives: To determine the frequency of common hematological abnormalities in patients with malaria. Study Design: A cross-sectional study. Place and Duration of the Study: Department of Medicine, Saidu Teaching Hospital, Swat Pakistan from November 2019 to May 2020. Material and Methods: A total of 137 patients of both genders aged between 18-60 years and who presented with malaria in emergency or outpatient department were analyzed. Ten cc blood was taken from all enrolled patients and sent to institutiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This can be explained by the invasion of hepatic cells by the parasite and the leakage of liver enzymes into the circulation. The increase in liver enzyme levels is also proportional to the severity of the malaria infection ( Megabiaw et al, 2022 ; Ahad et al, 2022 ). Liver dysfunction in malaria cases results from congestion, cellular inflammation, and sinusoidal blockage caused by the parasite ( Auta, Zakariyya & Everest, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…This can be explained by the invasion of hepatic cells by the parasite and the leakage of liver enzymes into the circulation. The increase in liver enzyme levels is also proportional to the severity of the malaria infection ( Megabiaw et al, 2022 ; Ahad et al, 2022 ). Liver dysfunction in malaria cases results from congestion, cellular inflammation, and sinusoidal blockage caused by the parasite ( Auta, Zakariyya & Everest, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 70 articles were further examined for eligibility, and 34 articles were excluded for the following reasons: no full-texts (n = 13), no records of articles (n = 8), unable to extract data (n = 6), non-English articles (n = 3), poster or conference abstracts (n = 2), reviews (n = 1), and an animal study (n = 1). A total of 37 studies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ] met the criteria and were included in the study. Another study [ 62 ] was identified from searches on Google Scholar.…”
Section: Resultsmentioning
confidence: 99%
“…Another study [ 62 ] was identified from searches on Google Scholar. Finally, 38 studies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] were included in the study for final analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations